A forgotten translation by Theodorus Gaza unveiled and its context - Galán Vioque, Guillermo (Byzantinische Zeitschrift, 2020)
The emigrant Byzantine humanist Theodorus Gaza (c. 1400 -1475) is well known as a teacher of Greek in various Italian cities, as a copyist of Greek manuscripts, and as a translator of Greek philosophical works into Latin. His undertakings as a translator of Latin works into Greek, among which his version of Cicero’s De senectute deserves mention, have gone relatively unnoticed. In this article we rediscover a largely forgotten translation of Cic. Fam. 1.1, despite it having been printed independently twice (Paris 1542 and 1548) and having been included as an example of translation in the oft reprinted manual of rhetorical exercises, Elementa rhetoricae (first printed in Basel in 1541), by the Lutheran Joachim Camerarius.